The hidden geographies of religious creativity: place-making and material culture in West London faith communities. (January 2019) - Gilbert, David; Dwyer, Claire; Ahmed, Nazneen; Cuch Graces, Laura; Hyacinth, Natalie
Religious activity, particularly as associated with what might be called everyday organized religion, has been unconsidered in recent discussions of the geographies and policies relating to creativity, and has been almost absent in the discipline of Geography's recent 'creative turn'. We argue both that religion has been given little or no attention in academic discussions of vernacular creativity, while arts policy as it developed in the United Kingdom in the post-war period has had a strongly secular focus. This continues in more recent policies and initiatives that have sought to promote the amateur and voluntary arts sectors. We explore the reasons for these absences, before turning to examples of strongly creative practice in a range of case studies, focused in a small area of suburban West London. These show a remarkable diversity of creativity including the design, construction and transformation of buildings and spaces for religious worship, but also in ritual, performance and the everyday practices of making sacred space. Our case studies include examination of performance and material culture in a Tamil-speaking Hindu temple, and in Roman Catholic, Anglican and Pentecostal churches. These include changes to architectural form, stained glass artwork, community craft projects, and musical performance and composition. We suggest that religious creativity has a hidden significance that has become more important in the United Kingdom's increasingly diverse cities and suburbs, and that significant population groups are marginalized in creativity debates and policies that focus on the secular arts. We also suggest that there are distinctive characteristics to what we describe as 'devotional creativity', particularly in different understandings of space, practice and experience.